Cytoskeleton rotation relocates mitochondria to the immunological synapse and increases calcium signals. Issue 5 (November 2016) - Maccari, Ilaria; Zhao, Renping; Peglow, Martin; Schwarz, Karsten; Hornak, Ivan; Pasche, Mathias; Quintana, Ariel; Hoth, Markus; Qu, Bin; Rieger, Heiko
Graphical abstract: Highlights: Mitochondria rotate together with the cytoskeleton towards the immunological synapse. Three-dimensional whole cell Ca 2+ model predicts Ca 2+ concentration in T cells. Global and local Ca 2+ signals depend on mitochondria and PMCA localization. Mitochondrial modulation of Ca 2+ signals is independent of Orai inactivation. Abstract: Ca 2+ microdomains and spatially resolved Ca 2+ signals are highly relevant for cell function. In T cells, local Ca 2+ signaling at the immunological synapse (IS) is required for downstream effector functions. We present experimental evidence that the relocation of the MTOC towards the IS during polarization drags mitochondria along with the microtubule network. From time-lapse fluorescence microscopy we conclude that mitochondria rotate together with the cytoskeleton towards the IS. We hypothesize that this movement of mitochondria towards the IS together with their functionality of absorption and spatial redistribution of Ca 2+ is sufficient to significantly increase the cytosolic Ca 2+ concentration. To test this hypothesis we developed a whole cell model for Ca 2+ homoeostasis involving specific geometries for mitochondria and use the model to calculate the spatial distribution of Ca 2+ concentrations within the cell body as a function of the rotation angle and the distance from the IS. We find that an inhomogeneous distribution of PMCA pumps on the cell membrane, in particular an accumulation of PMCA at the IS, increases the global Ca 2+ concentration and decreases the local Ca 2+ concentration at the IS with decreasing distance of the MTOC from the IS. Unexpectedly, a change of CRAC/Orai activity is not required to explain the observed Ca 2+ changes. We conclude that rotation-driven relocation of the MTOC towards the IS together with an accumulation of PMCA pumps at the IS are sufficient to control the observed Ca 2+ dynamics in T-cells during polarization.